Fossil Matter in the Geosphere - Schwarzbauer, Jan (Springer, 2015)
The first volume in this new text book series covers comprehensively relevant aspects related to the appearance and characterisation of fossil matter in the geosphere such as kerogen, oil, shales and coals. As organic geochemistry is a modern scientific subject characterized by a high transdisciplinarity and located at the edge of chemistry, environmental sciences, geology and biology, there clearly is a need for a flexible offer of appropriate academic teaching material on an undergraduat level addressed to the variety of students coming originally from different study disciplines. For such a flexible usage this textbook series' consists of different volumes with clear defined aspects and with manageable length.